The bright side of digitization: Assessing the impact of mobile phone domestication on left-behind children in China's rural migrant families - Tang, Jiamei; Wang, Ke; Luo, Yuming (Frontiers in Psychology, 2022)
This study examines the mobile phone practices of rural left-behind children (LBC) whose one or both parents migrate to cities for better earnings and the impact of such practices on migrant families in China. The study has used ethnographic approach by conducting participant observations and interviews of 21 LBC, residing in Guangren village, south China's Guangxi Autonomous Region. The study uses domestication theory to analyze these LBC's adoption of mobile phones in their daily routines and spaces in and out of their households. The key findings are as follows: (a) the LBC used mobile phones primarily to engage with their distant parent(s); (b) through collaborative efforts, they tried to enhance familial connections; and (c) they overcome the separation issue by co-participating in ongoing events, thus making the domestication of mobile phone a distant solving of real-world problems faced by migrant parent(s) and their LBC. The study concludes that LBC's innovative uses of mobile phones empowered them by building shared virtual space with their migrant parent(s), via which they handled the separation issue. In such shared virtual spaces, LBC's families have developed rich expressions of familial connections in various forms based on the limited perpetuate connectedness.